2007
DOI: 10.2478/v10032-007-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Quality of Cultivated and Natural Blueberry Fruit in Estonia

Abstract: Chemical Composition and Quality of Cultivated and Natural Blueberry Fruit in Estonia Nutrition studies suggest that blueberries help keep us healthy and these possible health benefits may be due to the antioxidant capacity as well as other natural compounds in blueberry fruit. Different taxa of Vaccinium species (Bilberry - Vaccinium myrtillus L.; lowbush blueberry - Vaccinium angustifolium Ait.; half-highbush blueberry - Vaccinium corymbosum x Vaccinium angustifolium ‘Northblue’ and ‘Northcoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
2
12
3
Order By: Relevance
“…The values founded in present study suggest that our climate and geographic conditions favored the accumulation of crude protein in blueberries, which is very interesting compared with the studies on "Duke" and "Bluecrop" cultivars carried out by Starast et al [14] in Estonia.…”
Section: Biometric and Nutritional Parameters In Blueberry Cultivarsmentioning
confidence: 41%
See 1 more Smart Citation
“…The values founded in present study suggest that our climate and geographic conditions favored the accumulation of crude protein in blueberries, which is very interesting compared with the studies on "Duke" and "Bluecrop" cultivars carried out by Starast et al [14] in Estonia.…”
Section: Biometric and Nutritional Parameters In Blueberry Cultivarsmentioning
confidence: 41%
“…Fruit weight shows a great variation within cultivars, whilst the fruit firmness seems to be directly related either to the harvest time or to cultivar and season [13]. The berry moisture content as well as its dry mass is significantly influenced by growing environmental conditions as reported by Starast et al [14]. The ripeness stage seems to be fundamental for the fruit quality.…”
Section: Introductionmentioning
confidence: 89%
“…In Estonia half-highbush blueberry is successfully cultivated in mineral soils (Starast et al 2002, Starast et al 2007a, lowbush blueberry has shown high productivity in peat soil (Vahejõe et al 2010, Paal et al 2011. Estonia is very rich in mires (Orru 1995) and peat production is a well-developed industry here.…”
Section: Manuscript Received May 2012 410mentioning
confidence: 99%
“…Climate conditions of North Europe are suitable for the lowbush (Vaccinium angustifolium Ait.) and half-highbush blueberry (V. corumbosum x V. angustifolium) cultivation (Bläsing 1989, Haffner and Vestrheim 1994, Paasisalo et al 1994, Starast et al 2007a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation